Strategi Pembelajaran Andragogi dalam Meningkatkan Kualitas Pembelajaran di Pusat Kegiatan Belajar Masyarakat Panrita - Eli, Eli; Ihwan Ridwan; Salmia Salama; Nursaidah, Nursaidah (FKIP UNSULTRA, 2026)
This study aims to analyze the implementation of andragogy learning strategies and their impact on improving the quality of learning among students at the Panrita Community Learning Center (PKBM). The research approach used was quantitative with a quasi-experimental method, involving 50 adult learners selected using purposive sampling techniques, then divided into experimental (andragogy) and control (conventional) groups. The independent variable in this study was the andragogy-based learning strategy, while the dependent variable was the quality of learning, which included active participation, material understanding, and practical skills. Data were collected through Likert-scale questionnaires, formative tests, and observation sheets, then analyzed using normality tests, homogeneity tests, and independent t-tests. The results of the descriptive analysis showed a more significant increase in posttest scores in the experimental group compared to the control group. The normality and homogeneity tests met parametric assumptions, while the independent t-test showed a significant difference between the two groups (p < 0.05). These findings confirm that andragogy strategies can significantly improve the quality of learning compared to conventional methods. Therefore, a learning approach that focuses on experience, learners' needs, and active participation has proven effective in non-formal education contexts. The implementation of andragogy at the Panrita Community Learning Center (PKBM) helps learners internalize the material more deeply and enhances practical skills and learning motivation, thus supporting the goal of lifelong learning. Ary, D., Jacobs, L. C., Sorensen, C. K., & Walker, D. A. (2021). Introduction to research in education (10th ed.). Cengage Learning. Broek, S., Kuijpers, M. A. C. T., Semeijn, J. H., & van der Linden, J. (2024). Conditions for successful adult learning systems at local level: Creating a conducive socio-spatial environment for adults to engage in learning. International Journal of Lifelong Education, 43(2–3), 200–223. https://doi.org/10.1080/02601370.2024.2338366 Creswell, J. W., & Creswell, J. D. (2023). Research design: Qualitative, quantitative, and mixed methods approaches (6th ed.). SAGE Publications. Fraenkel, J. R., Wallen, N. E., & Hyun, H. H. (2023). How to design and evaluate research in education (11th ed.). McGraw-Hill Education. Field, A. (2022). Discovering statistics using IBM SPSS statistics (6th ed.). SAGE Publications. Grotlüschen, A., Belzer, A., Ertner, M., & Yasukawa, K. (2024). The role of adult learning and education in the Sustainable Development Goals. International Review of Education, 70(2), 205–221. https://doi.org/10.1007/s11159-024-10066-w Hanifah, A., Setyowati, E., & Putra, R. H. (2025). Strategi pembelajaran orang dewasa di era digital. Paedagogi: Jurnal Kajian Ilmu Pendidikan, 17(1). https://jurnal.unimed.ac.id/2012/index.php/PAEDAGOGI/article/view/66714 Hanifah, A., Siregar, D., Toraja, J. A., Rahmadilah, N., & Lubis, P. R. (2025). Strategi pembelajaran orang dewasa di era digital untuk pendidikan luar sekolah. Paedagogi: Jurnal Kajian Ilmu Pendidikan, 11(1), 89–97. https://doi.org/10.24114/paedagogi.v11i1.66714 Johnson, R. B., & Christensen, L. (2020). Educational research: Quantitative, qualitative, and mixed approaches (7th ed.). SAGE Publications. Kholisussa’di, Rosyanafi, R. J., & Purwoko, B. (2025). Implementasi pendekatan andragogi untuk meningkatkan kemandirian santriwati di Pondok Putri Ridwan Anwarul Halimy Lombok Barat. Transformasi: Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 11(2), 312–321. https://doi.org/10.33394/jtni.v11i2.16044 Knowles, M. S. (2015). The adult learner: The definitive classic in adult education and human resource development (8th ed.). Routledge. Manurung, E., Hasibuan, J., Hutabarat, M. A., Fitra Suci, N. M., Simanjuntak, R. M. Y., Siburian, S. Z., & Sirait, W. W. P. (2025). Implementasi pendekatan andragogi di PKBM Budi Utomo. Jurnal Pendidikan Untuk Semua, 9(1), 60–66. https://doi.org/10.26740/jpus.v9n1.p60-66 Manurung, E., Pratama, I. G. A., & Salim, A. (2025). Implementasi pendekatan andragogi di PKBM Budi Utomo. JPUS: Jurnal Pendidikan Untuk Semua, 11(1). https://journal.unesa.ac.id/index.php/jpls/article/view/17585 Merriam, S. B. (2014). Adult learning: Linking theory and practice. Jossey Bass. Naumčiuk, T., & Baranova, S. (2025). Effective teaching methods for developing adult learners’ spoken foreign language skills: A systematic review. Andragogy Adult Education and Social Marketing, 5(5). https://doi.org/10.15503/andr2025.8 Rahmawati, D. (2023). Implikasi konsep andragogi dalam berbagai konteks pendidikan komunitas: Tinjauan literatur. Empowerment: Jurnal Ilmiah Pendidikan Luar Sekolah, 15(1), 23–36. https://e-journal.stkipsiliwangi.ac.id/index.php/empowerment/article/view/3916 Sari, I. N., Wahyudin, D., & Rusman, R. (2024). Analysis of e-learning implementation in adult learning (andragogy). Inovasi Kurikulum, 21(2), 1027–1040. https://doi.org/10.17509/jik.v21i2.66034 Shatila, S. L. (2024). Not alone when I’m feeling stressed: Online adult learner connection and retention. Adult Education Quarterly, 74(1), 43–61. https://doi.org/10.1177/07417136231184570 Sugiyono. (2021). Metode penelitian kuantitatif, kualitatif, dan R&D. Alfabeta. Sudjana, N. (2017). PKBM sebagai wadah pemberdayaan masyarakat: Perspektif pendidikan nonformal. Alfabeta. UNESCO. (2022). Global report on adult learning and education. UNESCO Publishing. Vaculíková, J., Kalenda, J., & Kočvarová, I. (2024). Participation in non-formal adult education within the European context: Examining a multilayer approach. Frontiers in Education, 9, 1380865. https://doi.org/10.3389/feduc.2024.1380865 Yahya, A. (2024). Penerapan prinsip andragogi dalam meningkatkan motivasi belajar peserta dewasa di PKBM. Jurnal Pendidikan Nonformal Indonesia, 16(1), 12–27. https://jurnal.ciptamediaharmoni.id/index.php/ptk/article/download/505/252 Yahya, A. I. B., Purnama, S., & Supeno, S. (2023). Eksplorasi prinsip andragogi dalam pendidikan orang dewasa: Sebuah studi kualitatif pada pendidikan formal dan non-formal di STIP Jakarta. PTK: Jurnal Tindakan Kelas, 5(1), 136–152.